The efficacy of ocular surface assessment approaches in evaluating dry eye treatment with artificial tears - Dorota H. Szczesna-Iskander; Maria Muzyka-Wozniak; Clara Llorens Quintana (Scientific Reports, 2022)
Abstract This study evaluates the effectiveness of objective techniques in assessing dry eye disease (DED) treatment compared with the subjective assessment commonly used in clinical practice. Thirty subjects were recruited for two visits separated by 28(± 3) days of treatment with artificial tears. A buttery of common subjective assessment methods were accompanied by a set of objective techniques including measurement of noninvasive tear film break-up time (NIBUT), lipid layer thickness (LLT), and quantitative evaluation of tear film surface quality and dynamics (TFD). Additionally, meibography was performed. Two commercially available videokeratoscopes and a prototype of a lateral shearing interferometer were used for the measurements. Both subjective and objective techniques showed a positive effect of artificial tears in DED treatment. Statistically significant improvements were observed in subjective symptoms (from P < 0.001 for Ocular Surface Disease Index, OSDI to p = 0.019 for tearing), conjunctival redness (P = 0.022), ocular staining (P = 0.012), fluorescein tear film break-up time (P = 0.015), NIBUT (P = 0.037), LLT (P < 0.001), and TFD (P = 0.048). In general, weak or statistically insignificant correlations were observed between subjective and objective assessment methods. The apparent lack of correlation between these methods might indicate the complementary character of objective techniques that likely assess other characteristics of ocular surface health than those assessed subjectively.